The Market Opportunities of Hotel Investment in Semarang - Pratiwi, Nadiar; Setijanti, Purwanita; Utomo, Christiono (Institut Teknologi Sepuluh Nopember, 2015)
Semarang is the capital city of Central Java with its greatest economic structure in the trading sector, including hotels and restaurants. Hotel investment in Semarang still has an opportunity. This research is needed to determine the best types of hotels that are possible to be built in Semarang. The method that is used in this research is surveyed by questionnaire and descriptive analysis using mean - standard deviation diagram. The types of hotels that are possible to be built in Semarang are the boutique hotel and the budget hotel with 2 star, 3 star and 4 star hotel as tourism hotel